Development of a Portable Gold Nanobipyramids-Based LSPR Sensor for Rapid Malathion Detection - Zarina Tukiran; Marlia Morsin; Nur Anis Aqilah Abdul Halim; Nur Liyana Razali; Nan Mad Sahar; Suratun Nafizah (International Journal of Nanoelectronics and Materials (IJNeaM), 2026)
Detecting pesticide residues using conventional laboratory methods is highly accurate; however, are not practical for onsite monitoring due to the requirement of complex procedures, long analysis times, and expensive equipment and maintenance. In this work, we present a portable and cost-effective sensor system for malathion detection. It is based on a localised surface plasmon resonance (LSPR) approach. The proposed system integrates gold nanobipyramids (GNBPs) as the sensing material, a SparkFun Triad Spectroscopy Sensor, and an Arduino UNO microcontroller. To monitor shifts in light wavelength in the presence of malathion, GNBPs with a surface density of approximately 69.623% and an average aspect ratio of 1.65 ± 0.06 are used. Later on, these spectral changes are captured by the spectroscopy sensor, processed by the Arduino UNO, and the LCD screen will display it in real time. The prototype is housed in a custom 3D-printed casing made from biodegradable PLA with a matte black finish to minimise stray light reflections and improve portability and ease of use. The experimental results show that the portable LSPR sensor provides a highly precise response at malathion concentrations as low as 0.5 mg/mL and offers a rapid and reliable alternative to standard laboratory techniques. The proposed device is suitable for agricultural workers as a practical tool for monitoring pesticide residues. This will support more sustainable agricultural practices, reducing environmental contamination, and lead to enhanced food safety.